Examining Stock Return Drivers in Garment and Textile Firms on the Indonesia Stock Exchange - Sihombing, Pardomuan; Melitana, Cyndi Loisa; Oktavia, Dinda (Research of Finance and Banking, 2023)
The problem of this research was entering the era “New Normal” has become an opportunity for economic players to invest in the capital market. Due to the unstable economic conditions, Therefore, investors need to conduct fundamental analysis in macro and micro economics so that their investments can obtain high stock returns the objective of this research was analysis of Factors Affecting Stock Returns with Firm Sizeas Moderating Variable in the Garment and Textile Industry Listed on the Indonesia Stock Exchange (IDX) 2016-2020. The methodology of this research was the collection of data using the scondary data by annual report firm Garment and Tekstil in BEI. The samples used in research as many as 16 firm with technique purposive sampling. The results of the study showed that there is no effect significant of ROE, DER, DER onstock returns. There is a significant negative effect of Interest Rates and Firm Size on stock returns. Variable Firm Size was also not proven to play a moderating role in the influence of ROE, DER, and CR, but Firm Size was able to significantly moderatinge the effect of interest rates on stock returns of garment and textile companies 2016-2020.